Prosa, música, poesia: a condição humana por Raul Seixas - Moura, José Gledson Nogueira (2020)
The current thesis has as its theme the human condition as it is expressed in the musical work of Raul Santos Seixas. Why should we think about the human condition based on art, poetry, music? Understanding poetry, theater, cinema, literature, music and the arts as human experiences that can contribute to an awareness and knowledge of the self, of the relationship with the other and of the insertion of the individual in society, the thesis assumes as its purpose to recover the necrotic parts of science in order to inject streams of creative, antiparadigmatic and critical thoughts and to build the possibility of architecting a new grammar of science, a new musical score of the knowledge narrative about the world and humanity through music. Starting from the consideration that, in the arts, there is a profound thought about the human condition, I problematize, through the poetry and music of Raul Seixas, his understanding of our condition of humanity. The research was developed in order to promote reflections on the constitution of the human being as biological and cultural, as universal and, at the same time, diverse and singular, as prosaic and poetic, reaffirming our existence as Sapiens sapiens demens. The work is stimulated and based on the phenomenon of culture and the consequent diversity of experiences that the human condition makes possible in life in society. While walking through the itinerary of Raul Seixas' life and work through his compositions and dialogue with the thoughts of authors such as Edgar Morin, Conceição Almeida, Edgard Carvalho, Nuccio Ordine, Giorgio Agamben, among others, I tension the figure of Raul as being the expression of prose, music, poetry.